Osteoblast adhesion on scaffolds of pla-plg-hydroxyapatite-chitosan-zinc by electroactivation (2012)
This paper presents results of the study of the phenomenon of electroactivation of system cell- polylactic acid (PLA) and polyglycolic acid (PLG) with additions of bioactive elements of chitosan (q), bioceramic (bc) and zinc. The main purpose was to explain the increase in the adhesion of cells as a result of the change in the hydrophilicity of the matrix cell regeneration and the variation in intracellular ion exchange, induced by the application of electric overpotential and bioactive elements additions to the polymers.